METHYLMALONIC ACID AND HOMOCYSTEIN SERUM IN DIAGNOSING MEGALOBLASTIC ANEMIA DUE TO COBALAMIN AND FOLATE DEFICIENCY IN TRAVEL MEDICINE - Made Gian Indra Rahayuda; Sianny Herawati (E-Jurnal Medika Udayana, 2014)
Anemia is a major global health problem, especially in developing countries. Anemia is a condition where the red blood cell mass and / or hemoglobin mass that circulating in the body was decreased to below normal level so it can not function well in providing oxygen to the body tissues. One of the most common type is megaloblastic anemia. Megaloblastic anemia is mostly caused by vitamin B12 (cobalamin) and folate deficiency. One of the causes of cobalamin and folate deficiency anemia is tropical sprue. Cobalamin deficiency anemia and folate deficiency anemia gives a similar symptom, but in cobalamin deficiency there is neuropathy symptoms. Normal serum folate is between 3-15 ng/mL. Normal folate erythrocyte is 150-600 ng/mL. In cobalamin deficiency, serum cobalamin decreased below the cut off point 100pg/mL (normally 100 - 400pg/mL). Other examination such as elevated homocysteine??, methylmalonic acid, or formioglutamic acid (FIGLU) in the urine can confirm the diagnosis of cobalamin and folic acid deficiency. There is no consensus on the cut-off point of homocysteine ??and MMA. Homocysteine ??has been considered to increase when the levels are above 12-14 ?mol /L in women and in the 14-15 ?mol/L. According to research by Robert et al in the case of cobalamin deficiency, serum tHcy> 15.0 ?mol/L. Most research considers the increase of MMA in cobalamin deficiency is> 0:28 ?mol / L, but the cut off point in circulation varies between 0:21 to 0:48 ?mol/L. MMA level is increased in serum and urine in cobalamin deficiency, whereas MMA normal in folate deficiency.